PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA VIDEO TUTORIAL DI SMK NEGERI 2 MAGELANG - Rokhana, Siti (LPPM IST AKPRIND Yogyakarta, 2021)
The low motivation and learning outcomes of class XI AKL 3 students at SMK Negeri 2 Magelang in the 2019/2020 Academic Year when participating in the Computer Accounting training course. Classroom action research (PTK) consists of two cycles. The first cycle of learning the PBL model was assisted by video tutorial media based on LCD projectors, while in the second cycle the learning of the PBL model was assisted by mobile-based video tutorials. Each cycle consists of four stages of research, namely planning, implementing actions, observing, and reflecting. The research results were analyzed using comparative descriptive followed by reflection. Comparative descriptive is done by comparing data on initial conditions, Cycle I and Cycle II, learning motivation and learning outcomes. The results of this study indicate that: First, learning the PBL model assisted by video tutorial media can increase learning motivation to analyze trading company financial reports in class XI AKL 3 students in the 2019/2020 academic year. The results of this study indicate that student learning motivation increased from the initial conditions 72.22% to 89.97% in the first cycle, and to 97.22% in the second cycle, or in the final condition increased by 25% from the initial conditions. Second, learning the PBL model assisted by video tutorial media can improve student learning outcomes Analyzing Commercial Company Financial Statements for class XI AKL 3 students for the 2019/2020 academic year. It is proven that the percentage of student learning completeness increases from the initial conditions of 61.11% to 80.56% in the first cycle and to 94.44% in the second cycle or in the final condition, it has increased by 33.33% from the initial conditions.